A revision of the southern South American stag beetles of the genus Sclerostomus Burmeister (Coleoptera: Scarabaeoidea: Lucanidae) - Paulsen, M. J. (Zootaxa, 2005)
Four species of stag beetles in the genus Sclerostomus Burmeister from southern South America (composing the subgenera Chileistomus Weinreich and Sclerostomulus Weinreich) are redescribed: S. cucullatus (Blanchard), S. nitidus Benesh, S. tuberculatus (Solier), and S. varasi Nagel. A key to the southern South American genera of Lucanidae and species of Sclerostomus are provided to facilitate identification. The classification of the genus within the Lucanidae is discussed. Nomenclatural problems within Sclerostomus are resolved, and the generic concept is fixed through a lectotype designation for the type species, S. costatus [Westwood]. Lectotypes are also designated for S. cucullatus (Blanchard) and S. tuberculatus (Solier). A neotype is designated for S. varasi, a validly described but heretofore misidentified species.Cuatro especies de los ciervos volantes del sur de Sudamérica en el género Sclerostomus (componiendo los subgéneros Chileistomus Weinreich y Sclerostomulus Weinreich Burmeister) son redescritas: S. cucullatus (Blanchard), S. nitidus Benesh, S. tuberculatus (Solier) y S. varasi Nagel. Se proporcionan claves para los géneros de Lucanidae del sur de Sudamérica y para el género Sclerostomus para facilitar su identificación. Se discute la posición del género dentro de Lucanidae. Se resuelven los problemas nomenclaturales en Sclerostomus y el concepto del género con la designación del lectotipo para la especie tipo, S. costatus [Westwood]. Se designan tambien lectotipos para S. cucullatus (Blanchard) y S. tuberculatus (Solier). Un neotipo se señala para S. varasi, una especie válida pero hasta ahora incorrectamente identificada.